Theological and Liturgical Content of the Rite of Animal Blessing - Smykowski, Krzysztof (Studia Warmińskie, 2023)
The aim of this paper is to describe the structure and theological content of the rite of blessing of animals. This rite follows the structure of the liturgy renewed after the Second Vatican Council and includes: the introductory rites, the liturgy of the word, the prayer of blessing and the conclusion. The method of liturgical hermeneutics was used. The semantic and structural study of liturgical texts made it possible to reveal the authentic theological richness of this rite. The blessing of animals is most often celebrated on the commemoration of St. Francis of Assisi or St. Roch.